Metáforas conceptuais visuais na linguagem dos anúncios da revista Veja - Silva, Flávia (2015)
The major goal of the research presented here is to identify the conceptual metaphors in ads published in Veja magazine, the main news weekly in Brazil. A corpus was collected to represent the ads both from a synchronic and a diachronic perspectives, covering nearly 40 years of the print history of the magazine. The research was inspired by Corpus Linguistics for both the design and the annotation of the corpus, but the principal analytic method employed was content analysis, which was used as a means to code in words the visual content of the ads. This coding was then interpreted in terms of the underlying conceptual metaphors. Conceptual metaphors are mappings from one conceptual domain to another, which structure our way of thinking and acting in the world (Lakoff and Johnson, 1980/2002). The study of visual metaphors is not widespread in the literature, and the study presented in this doctoral dissertation attempted to contribute to fill this gap. To achieve this goal we looked at three different types of products advertised in the magazine: alcoholic beverages, vehicles and cigarettes. The results showed that different semantic attributes and conceptual metaphor shape the ads for the different products over time, and that there are distinct patterns for the individual product types